The Myth of Resurrection in Ngugi’s a Grain of Wheat (British Journal of Multidisciplinary and Advanced Studies, 2024)
Our paper deal with ‘’The Myth of Resurrection in Ngugi’s ‘’A Grain of Wheat’’ in this, we have described the analysis of the myth of resurrection in the novel under criticism. This analysis has been achieved through the description of mythical aspects under mentioned. Apart from that, we have tried to brief down the cultural meaning of the myth under analysis. A Grain of wheat may be considered as novel tracing back the resurrection myth. Because it involves the idea of birth, death, and rebirth of Kenya. The imagery used by the author proves us that Kenya was a land given by MURUNGU (creator), invaded by the British, and reborn thanks to the sacrifices made by the local people. We can understand that Kenyan country is considered as symbol of all Africa land that is why African must arise and decolonizing their mind for their freedom from colonialists. Our readers will found same propositions which can be give us our liberation from the colonialist or others neocolonialism forms.